2021
DOI: 10.21203/rs.3.rs-135835/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Application of Failure Mode Effect Analysis (FMEA) to Improve Medication Safety in the Dispensing Process – A Study at A Teaching Hospital, Sri Lanka

Abstract: Background: Failure Mode Effect Analysis (FMEA) is a prospective, team based, structured process used to identify system failures of high risk processes before they occur. Medication dispensing is a risky process that should be analysed for its inherent risks using FMEA. Objectives: The objective of this study was to identify possible failure modes, their effects and causes in the dispensing process of a selected tertiary care hospital using FMEA. Methods: Two independent teams (Team A and Team B) of pharmacis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…At the first meeting the researcher introduced the FMEA process to team members with illustrations [ 13 , 41 ] and re-emphasised on the importance of a safety culture. To ensure that all were knowledgeable about the concept of a safety culture in the hospital, all the team members previously (Five months prior to this FMEA) attended a workshop on medication safety organised by the research team where various aspects of medication safety were emphasised [ 42 ]. This effort indicated that members of both teams were knowledgeable on medication safety and safety culture before engaging in FMEA.…”
Section: Methodsmentioning
confidence: 99%
“…At the first meeting the researcher introduced the FMEA process to team members with illustrations [ 13 , 41 ] and re-emphasised on the importance of a safety culture. To ensure that all were knowledgeable about the concept of a safety culture in the hospital, all the team members previously (Five months prior to this FMEA) attended a workshop on medication safety organised by the research team where various aspects of medication safety were emphasised [ 42 ]. This effort indicated that members of both teams were knowledgeable on medication safety and safety culture before engaging in FMEA.…”
Section: Methodsmentioning
confidence: 99%